INVESTIGATING THE EFFECT OF CIGARETTE SMOKING ON THE NKX3.1 AND TMPRSS2 GENES ASSOCIATED WITH MALE FERTILITY - Hamed Alsulami, Haneen (LIFE: International Journal of Health and Life-Sciences, 2024)
Cigarette's smoking has a wide negative impact on human health, and it's have been related to many serious issues like cancer, heart disease, respiratory system, and number of health problems. Also, smoking can affect fertility in men by affecting the sperm on several levels. Our research will investigate the genetic risk factors in male by focusing on NKX3.1 and TMPRSS2 genes related to male fertility and investigate the correlation between the gene’s polymorphisms of three groups (smokers, non-smokers, and infertile men). The NKX3.1 or NK3 homeobox 1 located on chromosome 8 is the first known prostate epithelium-specific marker it is an androgen regulated transcriptional and tumor suppressor gene this gene encodes for a homeobox-containing transcription factor and the transcription factor involved in development of the testes and prostate. there are not enough research data about NKX3.1 single nucleotide’s DNA variations and interaction with cigarettes smoking. The TMPRSS2 gene or transmembrane serine protease 2 is located on chromosome 21 is an endothelial cell surface gene encodes a protein that belongs to the serine protease family. TMPRSS2 is expressed in prostate epithelial cells and is needed for normal prostate function. It’s also expressed across the gastrointestinal (digestive) tract, such as in intestinal epithelial cells and across the respiratory tract. This gives TMPRSS2 gene an advantage to study or investigate gene expression influenced by lifestyle habits such as cigarettes smoke. Most of today research is confined to respiratory and cardiovascular system affected by cigarettes smoke but this research will investigate the relation between cigarettes smoking and fertility problems in men by selecting two fertility related genes (NKX3.1 and TMPRSS2) and analyzing single nucleotide polymorphisms (SNP) From 75 blood samples collected from 25 smokers ,25 control and 25 infertile\sub-fertile men. To amplify the regions of interest within the applied gene from extracted DNA, a polymerase chain reaction (qPCR) will be used, and ELISA technique to measure serum hormones level (Testosterone and prolactin and Estrogen). We expect this research to provide new information from a new aspect about the effect of cigarettes smoking on those genes and their relation to male infertility.